Efeitos anti-hiperalgésico e anti-inflamatório da Kielmeyera rugosa Choisy (Clusiaceae) em roedores - Melo, Mônica Santos de (2014)
Plants of the genus Kielmeyera, family Clusiaceae are used by the population of the Northeast of the Brazil in traditional medicine to treat various diseases, such as pain and inflammation diseases. A recent study demonstrated antitumor activity for K. rugosa, however, other pharmacological activities have never been studied, for example antihyperalgesic and anti inflammatory activities. Thus, the aim of this study was to evaluate the antihyperalgesic and anti - inflammatory effects of the methanol extract from the stems of K. rugosa (MEKR) in rodents. Swiss mice (25-35 g ) were divided into groups and subjected to treatment with MEKR (., 100, 200 and 400 mg/kg, oral administration, p.o.) , vehicle (0.9% saline solution + 0.2% Tween 80) or standard drug (i.p.). The hypernociception was evaluated at times 0.5 , 1, 2 , and 3 hours after administration (i.pl.) of carrageenan (CG; 300 mg/paw), tumor necrosis factor-α (TNF-α, 100 pg/paw), Prostaglandin E2 (PGE2; 100ƞg/pata) or dopamine (DA, 30 μg/paw) using the digital analgesymeter (von Frey). In the evaluation of anti-inflammatory activity two protocols were used, the first induced by GC (300 mg/well) at 4 hours after pleurisy which the full and differential counts were made of leukocytes as well as the dosage levels of TNF-α and IL-1β pleural lavage. In another protocol conducted to investigate the anti-inflammatory activity corresponded to paw edema induced by GC (1 %/40μL), the paw volume was measured with the aid of plethysmometer at 0-6h after CG. The cytotoxicity of MEKR was evaluated by the MTT colorimetric method. To determine the possible involvement of areas of the Central Nervous System (CNS), the animals were treated and ninety minutes, were anesthetized, perfused, the brains extracted and cut into the cryostat. The brain sections were subjected to immunofluorescence protocol for Fos protein. The motor coordination of the animal was assessed by the Rota Rod test (7 rpm, 180 s). The experimental protocols were approved by the ethics committee of the UFS (CEPA/UFS: 102/11) The results were expressed as mean ± standard error of the mean. Differences between groups were analyzed using the ANOVA one way followed by Tukey s test. The acute pretreatment with MEKR significantly inhibited hyperalgesia induced by nociceptive agents, CG, TNF-α, PGE2 and DA (p < 0.001). The MEKR inhibited the leukocyte recruitment into the pleural cavity (p < 0.01). This was due to the inhibition of leukocyte migration inhibition of neutrophils. The levels of cytokines, TNF-α (p < 0.01) and IL-1β (p < 0.001) were also reduced when the animals were treated with MEKR. MEKR decreased edema formation induced by CG (p < 0.001). However, MEKR showed no cytotoxic effect or change in motor coordination animals. In the Fos protein immunofluorescence test, MEKR showed that the olfactory bulb (p < 0.01), piriform cortex (p < 0.01) and periaqueductal gray (p < 0.001) for the active significantly of the CNS. Therefore, we conclude that MEKR has antihyperalgesic activity probably by activating the central nervous system areas associated with pain modulation and by reduction the production of proinflammatory cytokines, without traces of cytotoxicity.